(untitled) (REMUNOM, 2026)
Adolescence is a unique stage of human development, characterized by intense biological, psychosocial, and behavioral changes that directly affect oral health. It is a period of increased vulnerability to oral conditions such as dental caries, early periodontal diseases, and malocclusions, but also a critical window of opportunity for preventive and educational interventions with long-term impact. In this context, the present study aimed to analyze, through a narrative literature review, the particularities of adolescent oral health, discuss the relevance of oral health literacy, and reflect on the pertinence of creating and consolidating Odontohebiatry as a dental specialty focused on comprehensive adolescent care. A narrative review was conducted based on searches carried out between 2015 and October 2025 in the PubMed, Google Scholar, Virtual Health Library, and SciELO databases, using terms related to adolescent oral health and Odontohebiatry. Original articles addressing biological, behavioral, psychosocial, educational, and clinical aspects of adolescent oral health were included. After applying the eligibility criteria, 12 studies were selected for analysis. The findings indicate that adolescent oral health is strongly influenced by socioeconomic, territorial, familial, and psychological determinants, as well as by levels of oral health literacy. Low oral health literacy is associated with higher prevalence of dental caries, poorer oral hygiene, and reduced use of dental services, regardless of income level. In contrast, educational interventions grounded in behavioral theories have demonstrated effectiveness in improving knowledge, self-efficacy, and preventive behaviors among adolescents. Despite consistent scientific evidence highlighting the specific needs of this population, dental care for adolescents remains fragmented, often positioned between pediatric dentistry and adult dental care. The results support the consolidation of Odontohebiatry as a dental specialty grounded in scientific evidence and aligned with the clinical, educational, and psychosocial demands of adolescence. Such recognition may contribute to improving professional training, strengthening preventive and educational strategies, reducing inequalities, and promoting critical and autonomous self-care among adolescents. Furthermore, the absence of the term Odontohebiatry from controlled health descriptors underscores the need for advances in knowledge organization and institutional recognition of this emerging field.